Green Synthesis of Zinc Oxide Nanoparticles Using Salvia officinalis Leaf Extract and Their Photocatalytic and Antifungal Activities - May Abdullah Abomuti (MDPI AG, 2021)
The facile bio-fabrication of zinc oxide (ZnO) nanoparticles (NPs) is described in this study using an aqueous leaf extract of Salvia officinalis L. as an efficient stabilizing/capping agent. Biosynthesis of nanomaterials using phytochemicals present in the plants has received great attention and is gaining significant importance as a possible alternative to the conventional chemical methods. The properties of the bio-fabricated ZnONPs were examined by different techniques, such as UV-visible spectroscopy, X-ray diffraction spectroscopy (XRD), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and thermogravimetric/differential scanning calorimetry analysis (TGA/DTG). The photocatalytic activity of ZnONPs was investigated against methyl orange (MO) under UV light irradiation. Under optimum experimental conditions, ZnONPs exhibited 92.47% degradation of MO. Furthermore, the antifungal activity of bio-fabricated ZnONPs was determined against different clinical Candida albicans isolates following standard protocols of broth microdilution and disc diffusion assay. The susceptibility assay revealed that ZnONPs inhibit the growth of all the tested fungal isolates at varying levels with MIC values ranging from 7.81 to 1.95 µg/mL. Insight mechanisms of antifungal action appeared to be originated via inhibition of ergosterol biosynthesis and the disruption of membrane integrity. Thus, it was postulated that bio-fabricated ZnONPs have sustainable applications in developing novel antifungal agents with multiple drug targets. In addition, ZnONPs show efficient photocatalytic efficiency without any significant catalytic loss after the catalyst was recycled and reused multiple times.